Examining the Export-Led Growth Hypothesis: Empirical Evidence from Sudan - Mohamed Sharif Bashir; Ahmed Abdu Allah Ibrahim (Universitas Hayam Wuruk Perbanas, 2022)
The current study analyzes the relationship between Sudan's income growth and exports from 1970 to 2020. The system of equations using the Autoregressive Distributed Lag (ARDL) approach has been employed. The ARDL results showed that there exists a long-run relationship between the variables considered in the estimated model. The researchers observed a negative lagged error-correction term coefficient, which is highly significant in all cases supporting cointegration. The result reveals the existence of a long-run equilibrium relationship between GDP, export, import, labor force, and trade policy. This confirms that the export-led growth hypothesis is valid for Sudan. Thus, the most essential conclusion is that the economy’s export expansion strategy is completely dependent on the imports of raw materials and capital inputs and the kind of goods being exported. The coefficient of import is of significance, which offers strong support for the import compression hypothesis. The most important policy implication of the findings is the implementation of an appropriate and optimal approach that can boost exports to increase economic growth substantially. Policy-makers should focus on export diversification strategies and invest more in Sudan’s ability to provide value-added services to meet international export demand.